Phytochemical and pharmacological investigations of Egyptian clover, Trifolium alexandrinum L. - Ahmed, Qamar Uddin; Kaleem, Mohammed; Parveen, Nazneen; Khan, Nizam Ud Din (Universiti Putra Malaysia dan Jabatan Perhutanan Semenanjung Malaysia, 2006)
In continuation of our studies on the phytoconstituents of the Trifolium species (Fabaceae-Trifolieae), mostly occurring in India and other parts of the world, we have examined Trifolium alexandrinum L., which is also known as Barseem or Egyptian clover. Its aerial part is used as hay or pasture and seeds are used as an antidiabetic. Phytochemical data, obtained with several Trifolium species previously investigated, allowed the characterization of many secondary metabolites mainly consisting of flavonoids and aliphatic compounds structural types. The aim was to identify and characterize phenolic components in the leaves of T. alexandrinum for antimicrobial and antioxidant activities. Eight different flavonoids were detected after multistep chromatographic fractionation and preparative TLC using different solvent systems. The isolated flavonoids after purification from ethyl acetate extract were identified as 1) 5,7-dihydroxy-4'-O-methyl isoflavone, 2) 5,7,4'trihydroxy isoflavone, 3) 5,7,4'-trihydroxy flavone, 4) 5,7,3',4'-tetrahydroxy flavone, 5) apigenin 7-0-β-D-galactopyranoside, and 6) luteolin 7-0-β-glucoside by UV, IR, MS, IH-NMR, 13C-NMR analyses, direct comparison with their authentic samples and different chemical methods. Occurrence of monoflavonoids 3,4,5,6 from this plant is being reported for the first time. Further studies are still in progress to elucidate the structure of the remaining two phenolic compounds. The inhibitory potencies and capacities of different extracts against many gram positive and gram negative bacteria were also tested.